Association of a Single-Item Self-Rated Diet Construct With Diet Quality Measured With the Alternate Healthy Eating Index - Gago, Cristina M.; Lopez-Cepero, Andrea; O'Neill, June; Tamez, Martha; Tucker, Katherine; Orengo, José F. Rodríguez; Mattei, Josiemer (Frontiers in Nutrition, 2021)
Background: A single-item self-rated diet measure (SRD) may provide a quick, low-burden screener. However, assessment of its validity is limited. This study aimed to evaluate the association of an SRD construct with measured diet quality among adults in Puerto Rico (PR). Methodology: Participants (30-75y; n=247) of the PR Assessment of Diet, Lifestyle, and Diseases cross-sectional study (PRADLAD) reported SRD with a single question (“How would you describe your current dietary habits and diet quality?”) with a 5-point scale; excellent to poor. More complete diet quality was calculated using the Alternate Healthy Eating Index-2010 (AHEI), with 11 food and nutrient components assessed by food frequency questionnaire. Multivariable general linear models were used to test associations between SRD with AHEI and its components. Associations were also tested between recall SRD in youth and current AHEI. Results: Most participants (35.2%) self-rated diet as ‘good’, 13.8% as ‘excellent’, and 4.1% as ‘poor’, with remainder split between middle scale points. SRD was not significantly associated with AHEI, although participants with ‘excellent’ vs. ‘poor’ SRD had marginally higher AHEI (P=0.07). SRD was significantly associated with higher fruit intake (P=0.02), and marginally associated with intakes of vegetables (P=0.07) and long-chain fatty acids (P=0.07). Unexpectedly, AHEI was significantly higher among those reporting ‘poor’ SRD in young adulthood (P=0.01) or childhood (P=0.05). Conclusions: SRD may capture current diet quality at extreme intakes. Larger studies should confirm these findings and replicate them in other underrepresented populations. Further research should clarify the inverse associations between adult AHEI and earlier reported SRD.